Finite element simulation of the structural integrity of endothelial cell monolayers: A step for tumor cell extravasation. (1st February 2020) - Nieto, A.; Escribano, J.; Spill, F.; Garcia-Aznar, J.M.; Gomez-Benito, M.J.
Abstract: Cell extravasation is a crucial step of the metastatic cascade. In this process, the circulating tumor cells inside the blood vessels adhere to the cell monolayer of the blood vessel wall and passes through it, which allows them to invade different organs and complete metastasis. In this process, it is relevant to understand how the adhesions between cells that form the endothelial monolayer are broken, resulting in intra-cellular gaps through which tumor cells are able to extravasate the blood vessel wall. Within this process, we focus on studying the dynamics of cell-cell junctions rupture produced in the endothelial monolayer by the effect of Calcium waves. The regulation of this monolayer is of vital importance, not only in metastasis, but also in diseases such as pulmonary edema or atherosclerosis. In order to understand this rupture dynamics in greater depth, we propose a hybrid model that simulates endothelial cells as an elastic material and cell-cell adhesions of the monolayer by means of a catch bond law. We study the effects that the cell contraction caused by a Calcium wave presents on the endothelial monolayer depending on the diameter of the blood vessel. For this purpose, we develop a three-dimensional model to study the effect of the different blood vessel diameters. The results indicate that there are greater tractions on the joints located in vertices common to several cells. This led to the formation of openings in the endothelial monolayer, through which extravasation of tumor cells could occur. For the different geometries studied, no significant effect of the blood vessel diameter on the rupture of the adhesions of monolayer is observed.